1967
DOI: 10.1115/1.3614392
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Mean Absorption Coefficients for Infrared Radiation of Gases

Abstract: In this paper, a study is made on the calculation of appropriate mean absorption coefficients for the infrared radiation of gases. The Planck and Rosseland mean absorption coefficients for the optically thin and optically thick gases are expressed as functions of the spectroscopic and thermodynamic properties of the gas. Values of the Planck and Rosseland mean absorption coefficients are presented for carbon monoxide, carbon dioxide, and water vapor in the temperature range from 1000 to 5000 deg Rankine. To il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1968
1968
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Based on experiments, Cess and Mighdoll [4] have shown that, in the optically thin limit, these coefficients can be adequately Downloaded by [ (3) for carbon monoxide, carbon dioxide and water vapor where the temperature ratio T [T; = 1/2 and 2. Values of the Planck mean absorption coefficients for these gases have been reported by Abu-Rornia and Tien [5) in the range from 1000 R to 5000 R. Introducing the customary transformations…”
Section: Interaction Of Thermal Radiation In the Laminar Pipe Flow Ofmentioning
confidence: 96%
“…Based on experiments, Cess and Mighdoll [4] have shown that, in the optically thin limit, these coefficients can be adequately Downloaded by [ (3) for carbon monoxide, carbon dioxide and water vapor where the temperature ratio T [T; = 1/2 and 2. Values of the Planck mean absorption coefficients for these gases have been reported by Abu-Rornia and Tien [5) in the range from 1000 R to 5000 R. Introducing the customary transformations…”
Section: Interaction Of Thermal Radiation In the Laminar Pipe Flow Ofmentioning
confidence: 96%
“…Hence the radiative flux may be written as: ∇ · Q RAD = 4σ T 4 (a P,CO 2 + a P,H 2 O ); where σ is the Stefan-Boltzmann constant, and a P,CO 2 , a P,H 2 O are the Planck mean absorption coefficients for CO 2 and H 2 O, respectively. The values of absorption coefficients were obtained from Abu-Romia and Tien [18], and their accuracy was checked by using Grosshandler's narrow band model [19].…”
Section: Conservation Of Speciesmentioning
confidence: 99%
“…For intermediate values of the optical thickness of the emitting layer to reveal a natural process requires additional experimental studies, because in some cases it is possible to use absorption coefficients averaged Planck (approximation of an optically thin layer) or the Rosseland (zoom optically thick layer) [3].…”
mentioning
confidence: 99%